2014
DOI: 10.3389/fpsyg.2014.00287
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Test, Tower Test, and BRIEF-SR do not predict school performance of healthy adolescents in preuniversity education

Abstract: Executive functions (EF) such as self-monitoring, planning, and organizing are known to develop through childhood and adolescence. They are of potential importance for learning and school performance. Earlier research into the relation between EF and school performance did not provide clear results possibly because confounding factors such as educational track, boy-girl differences, and parental education were not taken into account. The present study therefore investigated the relation between executive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
1
18
0
2
Order By: Relevance
“…While multiple perspectives of self-reported behavior are recommended, especially for populations such as youth with ADHD who may be less aware of their own executive function deficits, the age of this typically developing group of adolescents in this sample was adequate to judge and evaluate their own behavior and perceptions. 53 Finally, demographic and health variables such as the presence and interaction of developmental disorders such as IQ performance, ADHD status, drug/alcohol use, and driving experience should be considered in future research to further understand the relation between executive function and problematic driving outcomes. Unfortunately, ADHD symptom severity or status was not assessed in our study sample.…”
Section: Discussionmentioning
confidence: 99%
“…While multiple perspectives of self-reported behavior are recommended, especially for populations such as youth with ADHD who may be less aware of their own executive function deficits, the age of this typically developing group of adolescents in this sample was adequate to judge and evaluate their own behavior and perceptions. 53 Finally, demographic and health variables such as the presence and interaction of developmental disorders such as IQ performance, ADHD status, drug/alcohol use, and driving experience should be considered in future research to further understand the relation between executive function and problematic driving outcomes. Unfortunately, ADHD symptom severity or status was not assessed in our study sample.…”
Section: Discussionmentioning
confidence: 99%
“…The BRIEF-SR has been used less frequently than the BRIEF in research. It may be that studies like that reported by Boschloo et al (2014) represent similar null findings that others find and do not publish, or that adolescents' insights into their own EFs remain an understudied area. Adolescents have been found to be able to rate their own behaviors accurately (Wichstrøm, 1995); nonetheless, individuals of many ages who are still developing an ability are often not so good at rating themselves on that ability (Dunning, Johnson, Ehrlinger, & Kruger, 2003), and the ability to monitor aspects of one's own performance is itself The European Educational Researcher | 177 an EF, so adolescents who are still developing the ability to monitor their own behaviors may not be so able to accurately rate themselves.…”
Section: Assessment Of Ef Through the Briefmentioning
confidence: 69%
“…Best et al (2011) investigated the relationships between EFs and academic achievement among a sample of over 2,000 children and adolescents using the Planning scale of the Cognitive Assessment System (Naglieri & Das, 1997); they found that EFs were moderately correlated with success in both math and reading achievement. Boschloo, Krabbendam, Aben, de Groot, and Jolles (2014), however, did not find a significant relationship between some subscores on a Dutch version of the BRIEF-SR and grades in Dutch, English, and mathematics; they also did not find that grades were predicted by behavioral measures of EFs from the Delis-Kaplan Executive Functions System.…”
Section: Assessment Of Ef Through the Briefmentioning
confidence: 75%
See 1 more Smart Citation
“…Nos artigos que utilizam instrumentos na avaliação de crianças e adolescentes, observou-se um interesse específico pela relação entre FE e o processo de aprendizagem, assim como pelas dificuldades encontradas neste (Boschloo et al, 2014;Lima et al, 2013;Freire et al, 2015;Pazeto, et al, 2014). Pode-se afirmar que o interesse por essa relação decorre do fato de que se demonstra que as habilidades executivas são preditoras de um bom desempenho na aprendizagem e que o prejuízo em algumas dessas habilidades pode levar a dificuldades de aprendizagem (Corso, Sperb, Jou, & Salles, 2013).…”
Section: Executive Function Performance Test (Efpt)unclassified